2005
DOI: 10.1186/1742-6413-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic small round cell tumour : Cytological and immunocytochemical features

Abstract: BackgroundDesmoplastic small round cell tumor (DSRCT) is a rare and highly aggressive neoplasm. The cytological diagnosis of these tumors can be difficult because they show morphological features quite similar to other small round blue cells tumors. We described four cases of DSRCT with cytological sampling: one obtained by fine needle aspiration biopsy (FNAB) and three from serous effusions. The corresponding immunocytochemical panel was also reviewed.MethodsPapanicolaou stained samples from FNAB and effusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…The common sites reported are pleura, paratesticular region, bone, soft tissue and ovary. 4 Although, in the present case the panel of markers used was sufficient enough to arrive at the right diagnosis, there are other markers said to be highly useful in difficult situations, especially in pediatric rhabdomyosarcomas. Most studies have shown rhabdomyosarcoma cells to express myogenin and MyoD1; the nuclear positivity of both these markers in ERMS is regarded as highly specific.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The common sites reported are pleura, paratesticular region, bone, soft tissue and ovary. 4 Although, in the present case the panel of markers used was sufficient enough to arrive at the right diagnosis, there are other markers said to be highly useful in difficult situations, especially in pediatric rhabdomyosarcomas. Most studies have shown rhabdomyosarcoma cells to express myogenin and MyoD1; the nuclear positivity of both these markers in ERMS is regarded as highly specific.…”
Section: Discussionmentioning
confidence: 86%
“…2 The embryonal rhabdomyosarcoma (ERMS) is common among children below 10 years, whereas, alveolar rhabdomyosarcoma (ARMS) affects chiefly, the adolescents and young adults. 1 Because of their cytomorphologic resemblance, both ERMS and ARMS have to be differentiated from other similar looking small round cell tumors (SRCTs) such as, peripheral neurectodermal tumor (PNET)/Ewing's sarcoma, lymphoma, 3 desmoplastic small round cell tumor (DSRCT), 3,4 and others. 3 Studies have shown that preoperative diagnosis of ERMS is possible solely on simple, noninvasive, cytologic methods using cytochemical and immunocytochemical techniques.…”
mentioning
confidence: 99%
“…Despite the fact that DSRCT is now a well-documented entity with several cytological reports in the literature, generally comprising case reports that include findings in both FNA material and ascitic/pleural effusions [6,7,8,9,17,18,19,20,21,22], its diagnosis is still usually established by histopathological examination.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor cells demonstrate a high nuclear-cytoplasmatic ratio, oval to round hyperchromatic nuclei with a finely granular chromatin pattern and inconspicuous nucleoli, smooth or irregular nuclear membranes and frequent nuclear molding. The cytoplasm is scant to moderate, palely amphophilic to eosinophilic and occasionally vacuolated [3,4,5,6,7,8,9]. …”
Section: Introductionmentioning
confidence: 99%
“…The cytological diagnosis of this tumor has only ocurred in a few cases, and most of these cases were based on fine-needle aspiration cytology 2-5. Presented herein is a case of cytological finding of DSRCT with extensive glandular differentiation using peritoneal-washing and pleural-effusion ThinPrep.…”
mentioning
confidence: 99%